Financial Performance and Risk - Rahmawan, Rizal; Bakar, Armi (Publikasi Indonesia, 2023)
When it comes to consumer-goods companies in particular, having shareholders who invest in the company's stock is a major factor in the company's success. In which the investors naturally demand return of their money. Where annual financial reports provide shareholders with a window into firm performance and allow them to steer its future direction. However, in the process of developing any organization, there are a number of dangers that must be dealt with quickly so as to not have a long-lasting unfavorable influence. This is why the effects of financial performance and risk on stock returns of consumer goods companies listed on the Indonesia Stock Exchange for the period 2016-2021 is of interest to scholars. The research aims to answer the question,